A kind of black optical glass transparent to near infrared and its application

By using Cr2O3, CoO, CeO2 and MnO2 in a specific proportion of as coloring components in the oxide glass, the problem of insufficient chemical stability and hardness of near-infrared glass in the prior art is solved, and a high transmittance near the wavelength of 905nm is achieved and multi-band performance improvements, suitable for near-infrared filtering.

CN118026525BActive Publication Date: 2024-12-24湖北戈碧迦光电科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410093907.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2024-12-24
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

The existing near-infrared transmittance glass has shortcomings in terms of chemical stability and hardness, especially in the 905nm band laser transmittance requirements cannot be met, and unevenness and colored spots are prone to occur during the heat treatment process, which limits stable production.

Method used

Using specific contents of oxide glass formulas, including Cr2O3, CoO, CeO2 and MnO2 as coloring ingredients, the ratio of these ingredients is adjusted to obtain black glass that can absorb UV, visual area and far infrared to ensure high transparency around the wavelength of 905nm and improve the multi-band transmittance and chemical stability of the glass by optimizing the proportion of other components in the oxide glass.

Benefits of technology

It achieves high transmittance and good chemical stability around the wavelength of 905nm, avoids the problem of unevenness in the heat treatment process, is suitable for stable production, and improves the hardness, water and acid resistance of the glass, and meets the performance of multi-bands. Require.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118026525B_ABST
    Figure CN118026525B_ABST
Patent Text Reader

Abstract

The present invention discloses a near-infrared transparent black optical glass and its application, belonging to the technical field of colored glass. The black optical glass is composed of oxide glass and coloring components. The coloring components include the following components in terms of the mass percentage of the coloring components to the oxide glass: Cr2O3: 0.15% to 0.25%; CoO: 0.05% to 0.10%; CeO2: 1% to 5%; MnO2: 0 to 1%. The present invention adopts a specific content of coloring components, which can absorb ultraviolet, visible and far-infrared bands, and maintain excellent transmittance in the near-infrared, especially at a wavelength of 905nm, has clear transmittance to the target band, has good chemical durability, does not require coloring engineering such as heat treatment, and is suitable for stable production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of colored glass, and in particular to a near-infrared transparent black optical glass and application thereof. Background Art

[0002] With the development of automotive laser radar, black glass with lasers around 905nm band needs to have better chemical stability and hardness requirements. In the past, there was a big difference between near-infrared transmission filter glass such as colloidal colored glass CdS-CsSe glass and colored ion colored glass Mn-Cr glass. CdS-CsSe glass needs a heat treatment process to precipitate colloids after glass melting and cooling. The initial purpose is to have spectral transmittance, but it does not only require a heat treatment process. During the melting process, the volatile volatilization of S, Se, etc. is fierce, making it difficult to obtain homogeneous glass, and the uneven glass is prone to color spots caused by heat treatment. It is difficult to obtain high-quality glass with a certain transmittance, which is not conducive to stable production. In addition, the chemical durability of this glass is generally poor and cannot meet the requirements in recent years. Mn-Cr glass has a high transmittance in the mid-infrared, but a low transmittance in the 800-1050nm band, which does not meet the 905nm laser transmittance requirements.

[0003] The Japanese invention patent with publication number JPH07126036A provides a near-infrared transmission black filter glass, which contains oxide glass and specific coloring components, so as to have clear spectral transmission performance and improve chemical durability. The glass used for the near-infrared transmission black filter contains 0.2-3.0wt.% Cr2O3 and 0.2-4.5wt.% CoO as coloring components. The near-infrared transmission black glass has clear spectral transmittance, does not require color-producing engineering such as heat treatment, and is suitable for stable production. However, its formula range is wide, lacks specific chemical stability indicators, and does not explore the cutoff of the ultraviolet part of the glass and the glass hardness test. In actual use, it is difficult to meet the transmittance requirements and other performance requirements of multiple bands, which limits the use of the glass.

[0004] Therefore, providing a near-infrared transparent black optical glass with good comprehensive performance is of great significance for expanding its application. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a near-infrared transparent black optical glass is provided, wherein the black optical glass is composed of oxide glass and a coloring component, and the coloring component includes the following components in terms of the mass percentage of the coloring component to the oxide glass:

[0006] Cr2O3: 0.15%~0.25%;

[0007] CoO: 0.05%~0.10%;

[0008] CeO2: 1%~5%;

[0009] MnO2: 0~1%.

[0010] The invention concept of the present invention using the above coloring components is that Cr2O3, CoO and CeO2 are introduced into the oxide glass. Through their specific proportions, it is easier to obtain black glass that can absorb ultraviolet, visible area and far infrared, and has clear transmittance near the wavelength of 905nm, and the glass has good stability. The amount of components will affect the transmittance of glass in different bands. The transmittance index under the multi-band technical requirements of the present invention will be affected by the amount of the components themselves and the amount of other components. It is difficult to achieve the expected goal through deduction based on the prior art. The reason why the present invention is designed to use the above component content is that if the relative content of Cr2O3 is lower than 0.15%, a transmittance peak will appear near the wavelength of 450nm, and the transmittance will be higher than 5%; if it exceeds 0.25%, the transmittance near the wavelength of 905nm will not reach the technical indicator of 89%. For CoO, when the weight is less than 0.05%, the transmittance at wavelengths of 550-570nm and 670-690nm will be higher than 5%, affecting its use; when the CoO content exceeds 0.10%, the transmittance near the 905nm wavelength will not reach 89%. Similarly, when the CeO2 content is less than 1%, the transmittance below the 420nm wavelength will exceed the design target of 10%; when the CeO2 content is greater than 5%, it will affect the transmittance near the 905nm wavelength. When the MnO2 content is higher than 1%, it will also affect the transmittance near the 905nm wavelength.

[0011] Preferably, the oxide glass comprises the following components:

[0012] SiO2: 55%~68%;

[0013] Al2O3: 0-25%;

[0014] RO: 0~8%;

[0015] ZnO: 0-10%;

[0016] TiO2: 4-10%;

[0017] MO: 17%-22%;

[0018] F: 0.5%~1.2%;

[0019] Clarifying agent: 0-1%;

[0020] The sum of the mass percentages of the above components is 100%;

[0021] Wherein, RO represents alkaline earth oxide, including 0-3% BaO, 0-5% CaO and the balance MgO;

[0022] MO represents alkali metal oxides, including 5% to 12% Na2O, 5% to 10% K2O and 0 to 2% Li2O.

[0023] In practical applications, the components in the oxide glass, such as Al2O3, CaO, ZnO, Li2O, etc., can be adaptively added and adjusted according to the short-wave and long-wave transmittance, the chemical stability requirements of the glass, the viscosity during preparation, and the need for chemical strengthening, which brings more flexible options for the use of the black optical glass of the present invention.

[0024] Further preferably, the clarifier includes at least one of Na2SO4, NaCl, CaSO4, SnO2, and Sb2O3.

[0025] Preferably, the transmittance of the black optical glass at a thickness of 6 mm in the wavelength range of 890 to 910 nm is greater than 89%.

[0026] Further preferably, the transmittance of the black optical glass at a thickness of 6 mm in the wavelength range of 860 to 930 nm is greater than 89%.

[0027] Preferably, the transmittance of the black optical glass at a thickness of 6 mm is less than 10% in the wavelength range of 350 to 690 nm.

[0028] More preferably, the transmittance of the black optical glass in the wavelength range of 350-690 nm is less than 5% at a thickness of 6 mm.

[0029] Preferably, the transmittance of the black optical glass at a thickness of 6 mm in the wavelength range of 250 to 350 nm is less than 5%.

[0030] More preferably, the transmittance of the black optical glass in the wavelength range of 250-350 nm is 0% at a thickness of 6 mm.

[0031] Preferably, the water resistance classification level of the black optical glass tested according to JB / T 10576 standard is not lower than level 2.

[0032] Further preferably, the water resistance classification level of the black optical glass is level one.

[0033] Preferably, the acid resistance classification level of the black optical glass tested according to JB / T 10576 standard is not lower than level 2.

[0034] Further preferably, the acid resistance classification level of the black optical glass is level one.

[0035] Preferably, the black optical glass needs to meet the Kirkmar hardness of not less than 485.10 7 Performance index of Pa.

[0036] Further preferably, the black optical glass has a Kirkmar hardness of ≥500·10 7 Pa.

[0037] Preferably, the black optical glass needs to meet the performance indicators of elastic modulus not less than 70 GPa and shear modulus not less than 30 GPa.

[0038] Further preferably, the elastic modulus of the black optical glass is ≥75 GPa.

[0039] According to the composition of the glass, its performance will fluctuate within a certain range. The above preferred parameters are based on the best application technical indicators of black optical glass under different usage requirements; under further optimized parameter range, black optical glass will have better comprehensive performance and play the best function.

[0040] Black optical glass appears black when in use, has good chemical stability, high hardness, and does not require production processes such as heat treatment and coating. It can stably produce black filter glass with near-infrared transmittance around 905nm. When in use, it has high transmittance to lasers in the near-infrared band around 905nm, and low transmittance to ultraviolet, visible and far-infrared bands. It can well shield the optoelectronic devices behind the window, filter the light of non-laser application wavelengths, and make the system have a high signal-to-noise ratio. It can be used, for example, to enhance the detection capability of laser radars.

[0041] In the second aspect of the present invention, there is provided an application of the black optical glass of the first aspect of the present invention, specifically, an application as near-infrared transmitting glass in the field of filtering.

[0042] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0043] The present invention provides a black optical glass, which adopts a specific content of coloring components, can absorb ultraviolet, visible and far infrared bands, and maintain excellent transmittance in near infrared, especially at a wavelength of 905nm, has clear transmittance to a target band, has good chemical durability, does not require color development processes such as heat treatment, and is suitable for stable production.

[0044] The present invention also provides an application of black optical glass, which has good application prospects in the field of filtering as near-infrared transmitting glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is the transmittance curve of black optical glass in the spectrum (250-2500nm) with a thickness of 6mm. DETAILED DESCRIPTION

[0046] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0047] In the following embodiments:

[0048] The transmittance test equipment used was PerkinElmer (Lambda 1050+), and the thickness of the tested samples was 6 mm;

[0049] Black optical glass is made by common methods in this field, and no color-producing processes such as heat treatment are used in the process.

[0050] Example 1

[0051] The components and contents of the black optical glass in this embodiment are as follows:

[0052] SiO2: 62%;

[0053] Sb2O3: 0.22%;

[0054] K2O: 8.5%;

[0055] Na2O: 6.6%;

[0056] ZnO: 8.2%;

[0057] F: 0.9%;

[0058] TiO2: 7%;

[0059] Al2O3: 3.5%;

[0060] Li2O: / ;

[0061] BaO: / ;

[0062] CaO: / ;

[0063] Cr2O3: 0.3%;

[0064] CoO: 0.07%;

[0065] CeO2: 2.8%;

[0066] MnO2: 0.3%.

[0067] In the above components, “ / ” represents the content is 0%.

[0068] In actual preparation, due to the purity of raw materials and the inherent error of equipment, the actual total mass percentage will fluctuate within an acceptable range above and below the theoretical value (100%). The mass percentage of the above components totals 100.29%, with extremely low deviation, and can be regarded as being proportioned according to the theoretical value.

[0069] Example 2

[0070] The components and contents of the black optical glass in this embodiment are as follows:

[0071] SiO2: 55.5%;

[0072] Sb2O3: 0.24%;

[0073] K2O: 6.8%;

[0074] Na2O: 8.8%;

[0075] ZnO: / ;

[0076] F: 1%;

[0077] TiO2: 5%;

[0078] Al2O3: 14%;

[0079] Li2O: 1%;

[0080] BaO: 2.2%;

[0081] CaO: 4%;

[0082] Cr2O3: 0.18%;

[0083] CoO: 0.06%;

[0084] CeO2: 2%;

[0085] MnO2: / .

[0086] In the above components, “ / ” represents the content is 0%.

[0087] In actual preparation, due to the purity of raw materials and the inherent error of equipment, the actual total mass percentage will fluctuate within an acceptable range above and below the theoretical value (100%). The mass percentage of the above components totals 100.78%, with extremely low deviation, and can be regarded as being proportioned according to the theoretical value.

[0088] Example 3

[0089] The components and contents of the black optical glass in this embodiment are as follows:

[0090] SiO2: 61.5%;

[0091] Sb2O3: 0.24%;

[0092] K2O: 8.8%;

[0093] Na2O: 8%;

[0094] ZnO: 5.9%;

[0095] F: 1%;

[0096] TiO2: 6.6%;

[0097] Al2O3: 4.8%;

[0098] Li2O: / ;

[0099] BaO: / ;

[0100] CaO: / ;

[0101] Cr2O3: 0.18%;

[0102] CoO: 0.07%;

[0103] CeO2: 2.5%;

[0104] MnO2: 0.5%.

[0105] In the above components, “ / ” represents the content is 0%.

[0106] In actual preparation, due to the purity of raw materials and the inherent error of equipment, the actual total mass percentage will fluctuate within an acceptable range above and below the theoretical value (100%). The mass percentage of the above components totals 100.09%, with extremely low deviation, and can be regarded as being proportioned according to the theoretical value.

[0107] Example 4

[0108] The components and contents of the black optical glass in this embodiment are as follows:

[0109] SiO2: 61.5%;

[0110] Sb2O3: 0.24%;

[0111] K2O: 7.8%;

[0112] Na2O: 9%;

[0113] ZnO: 5.9%;

[0114] F: 0.8%;

[0115] TiO2: 7%;

[0116] Al2O3: 3.8%;

[0117] Li2O: 0.9%;

[0118] BaO: / ;

[0119] CaO: / ;

[0120] Cr2O3: 0.18%;

[0121] CoO: 0.07%;

[0122] CeO2: 3%;

[0123] MnO2: 0.4%.

[0124] In the above components, “ / ” represents the content is 0%.

[0125] In actual preparation, due to the purity of raw materials and the inherent error of equipment, the actual total mass percentage will fluctuate within an acceptable range above and below the theoretical value (100%). The mass percentage of the above components totals 100.59%, with extremely low deviation, and can be regarded as being proportioned according to the theoretical value.

[0126] Example 5

[0127] In this embodiment, the optical properties of the prepared black optical glass are measured, and the transmittance curve is as follows: Figure 1 The transmittance under different typical wavelength ranges is shown in Table 1.

[0128] Table 1:

[0129]

[0130] According to the above test results, the black optical glass of the present invention can absorb ultraviolet, visible and far infrared bands, and maintain excellent transmittance in near infrared, especially at 905nm wavelength, and has clear transmittance to the target band.

[0131] Example 6

[0132] In this example, the physical performance indicators of the prepared black optical glass were measured to explore its comprehensive performance in application:

[0133] Water resistance and acid resistance are measured according to the method and steps specified in JB / T 10576-2006 "Test method for chemical stability of colorless optical glass - Powder method";

[0134] Kirschner hardness is measured according to the method and steps specified in GB / T 7962.18-2010 "Test methods for colorless optical glass Part 18: Kirschner hardness";

[0135] The elastic modulus, shear modulus and Poisson's ratio are measured according to the method and procedures specified in GB / T 7962.6-2010 "Test methods for colorless optical glass Part 6: Young's modulus, shear modulus and Poisson's ratio";

[0136] The remaining parameters were measured according to the standard test methods commonly used in the field, and the test results of the performance indicators are shown in Table 2.

[0137] Table 2:

[0138]

[0139] The above test data show that the black optical glass of the present invention has good mechanical properties and chemical durability, and meets the use requirements of a filtering material that transmits near infrared rays.

[0140] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A near-infrared transparent black optical glass, the black optical glass is composed of oxide glass and a coloring component, characterized in that: Calculated by the mass percentage of the coloring component to the oxide glass, the coloring component includes the following components: Cr2O3: 0.15%~0.25%; CoO: 0.05%~0.10%; CeO2: 1%~5%; MnO2: 0~1%; The oxide glass includes the following components: SiO2: 55%~68%; Al2O3: 0~25%; RO: 0~8%; ZnO: 0~10%; TiO2: 4~10%; MO: 17%~22%; F:0.5%~1.2%; Clarifying agent: 0~1%; The sum of the mass percentages of the above components is 100%; Among them, RO stands for alkaline earth oxide, including 0~3% BaO, 0~5% CaO and the balance MgO; MO stands for alkali metal oxides, including 5%~12% Na2O, 5%~10% K2O and 0~2% Li2O.

2. The black optical glass according to claim 1, characterized in that: The clarifier includes at least one of Na2SO4, NaCl, CaSO4, SnO2, and Sb2O3.

3. The black optical glass according to claim 1, characterized in that: The black optical glass has a transmittance of more than 89% in the 860-930 nm wavelength range at a thickness of 6 mm.

4. The black optical glass according to claim 1, characterized in that: The transmittance of the black optical glass in the wavelength range of 350-690 nm is less than 10% at a thickness of 6 mm.

5. The black optical glass according to claim 1, characterized in that: The transmittance of the black optical glass in the 250-350nm band is less than 5% at a thickness of 6mm.

6. The black optical glass according to claim 1, characterized in that: The water resistance classification level of the black optical glass tested according to JB / T10576 standard is not lower than Grade 2; the acid resistance classification level is not lower than Grade 1.

7. The black optical glass according to claim 1, characterized in that: The black optical glass must have a Kirkmar hardness of not less than 485.10 7 Performance index of Pa.

8. The black optical glass according to claim 1, characterized in that: The black optical glass must meet the performance indicators of an elastic modulus of not less than 70 GPa and a shear modulus of not less than 30 GPa.

9. An application of the black optical glass according to any one of claims 1 to 8, characterized in that: Application as near-infrared transmitting glass in filtering field.

Citation Information

Patent Citations

  • Gray green sunglasses glass suitable for lattice-method process production

    CN101643317A

  • Infrared transmitting glass

    CN111148725A